Polysaccharide hemostatic powder to prevent bleeding after endoscopic submucosal dissection in high risk patients: a randomized controlled trial - Jung, Da Hyun; Moon, Hee Seok; Park, Chan Hyuk; Park, Jun Chul (Endoscopy, 2021)
Background Bleeding after endoscopic submucosal dissection (ESD) is a severe adverse event. Several methods to prevent post-ESD bleeding (PEB) have been introduced; however, they have not been widely used because of technical difficulties. We aimed to investigate whether polysaccharide hemostatic powder (PHP), which is very easy to apply, can prevent early post-ESD bleeding, especially in patients with a high risk of post-ESD bleeding.Methods This was a prospective, multicenter, randomized, open-label, controlled trial. Patients with a high risk for post-ESD bleeding were enrolled. Patients with gastric neoplasms in whom the resected specimen size was expected to be > 40 mm and those who were regularly taking antithrombotic agents were defined as high risk patients. Patients were randomly assigned to the PHP or control groups. Results Between May 2017 and September 2018, 143 patients were enrolled (PHP group, 73; control group, 70). The total post-ESD bleeding rate was 6.3 % (PHP group, 5.5 % vs. control group, 7.1 %; P = 0.74). There was no bleeding within 7 days after ESD in the PHP group. Continued antithrombotic use was an independent risk factor for post-ESD bleeding. In subgroup analysis excluding the patients who continued to take antithrombotic agents (n = 129) during ESD, the rate of post-ESD bleeding tended to be lower in the PHP group than in the control group (0 % vs. 6.3 %; P = 0.06).Conclusion PHP did not demonstrate a significant effect on the prevention of post-ESD bleeding in this study. Further larger scale, randomized controlled trials are needed to confirm this.